(untitled) (Research, Society and Development, 2021)
Retelling stories and answering questions is important for social and academic development. In the case of children with Autism Spectrum Disorder (ASD), the learning may be challenging. Previous research used customized stories with logical sequence games. The materials consisted of pictures (scenes) and phrases about them. This study was conducted with two children with ASD. Two teaching procedures to retell stories were compared (regular chaining and back-to-front chaining) after they were presented to them. Two four-part stories were established for each child. During teaching, each child could retell each part of a story from the beginning and, if necessary, visual and verbal prompts were provided (regular chaining). With the other story, initially, the first three parts were presented to each child, but the last could be retold without prompts. When this happened, prompts to the penultimate part were also omitted. This was replicated over the other parts until it was possible to retell the whole story without prompts. The regular chaining was more efficient for both children. In parallel, the effects of two prompts (tacts and echoics) were assessed on answering questions. For one child, tact prompts were more efficient and, for the remaining one, the contrary. It was discussed the possible influence of a previous exposure history to a type of procedure regarding its relative efficiency. It was suggested the possibility that teaching through adapted stories may influence a later better engagement with non-adapted histories in context of shared reading, favoring school inclusion processes.